THE USE OF INTERACTIVE TEACHING METHODS IN MEDICAL EDUCATION IN HIGHER EDUCATION INSTITUTIONS - Qurbonova Munisa,; Maksudova Malika,; Nadirova Yulduz, (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract:  Modern  medical  education  faces  the  challenge  of  preparing  highly competent, critical-thinking, and patient-centered healthcare professionals. Traditional lecture-based teaching methods are increasingly considered insufficient for developing clinical  reasoning,  communication  skills,  and  lifelong  learning  habits  required  in contemporary medical practice. This article explores the role of interactive teaching methods in higher education for medical students. Based on scientific literature and international educational standards, the paper analyzes the effectiveness of interactive methods  such  as  problem-based  learning,  case-based  learning,  simulation-based education, team-based learning, and digital interactive tools. The findings demonstrate that interactive methodologies significantly improve students’ academic performance, clinical  competence,  motivation,  and  professional  skills.  The  article  concludes  that integrating  interactive  teaching  methods  into  medical  curricula  is  essential  for improving the quality of medical education.